Forskolin effect on the cryosurvival of in vitro-produced bovine embryos in the presence or absence of fetal calf serum - Paschoal, Daniela Martins [UNESP]; Sudano, Mateus Jose [UNESP]; Guastali, Midyan Daroz [UNESP]; Maziero, Rosira Rosria Dias [UNESP]; Crocomo, Letcia Ferrari [UNESP]; Magalhaes, Luis Carlos Ona [UNESP]; Rascado, Tatiana da Silva [UNESP]; Martins, Alicio [UNESP]; Landim-Alvarenga, Fernanda Da Cruz [UNESP] (Cambridge University Press, 2014)
The objective of this study was to assess the viability and cryotolerance of zebu embryos produced in vitro with or without the addition of fetal calf serum (FCS) and forskolin (F). Embryos produced in vivo were used as a control. Presumptive zygotes were cultured in modified synthetic oviductal fluid supplemented with amino acids (SOFaa), bovine serum albumin (BSA) and with (2.5%) or without (0%) FCS. On day 6 of growth, the embryos from each group were divided into treatments with or without 10 mu M F to induce embryonic lipolysis, comprising a total of four experimental groups: 2.5% FCS, 0% FCS, 2.5% + F and 0% + F. For vitrification, embryos were exposed to vitrification solution 1 (5 M EG (ethylene glycol)) for 3 min and then transferred to vitrification solution 2 (7 M EG, 0.5 M galactose solution and 18% (w/v) Ficoll 70) before being introduced to liquid nitrogen. The presence of FCS in the culture medium resulted in the production of embryos with a similar rate of damaged cells compared with in vivo-produced embryos. After vitrification, the 2.5% FCS group had a significantly higher rate of damaged cells when compared with the other groups (P < 0.05). The results of this experiment indicated that the omission of FCS and the addition of forskolin do not have deleterious effect on embryo production rates. In addition, embryos produced in the presence of FCS had greater sensitivity to cryopreservation, but this effect was reversed when forskolin was added to the medium, which improved embryo survival without affecting embryo development and quality after vitrification.
Keywords: Forskolin; Vitrification; In vitro production; Embryo; Fetal calf serum